Strengthening Togetherness with Subuh Education and Anti-Bullying Education in Nagari Koto Baru - Frisdianti, Tiara; Rahmadani, Melinia; Khan, Omar; Mokoena, Thabo (Darussalam: Journal of Psychology and Educational, 2025)
This article discusses the importance of strengthening togetherness through early education and anti-bullying education as a solution to facing the social challenges faced by today's young generation. In the increasingly complex context of globalization, bullying has become an urgent issue, having a negative impact on mental health and social relationships. Dawn education, as a learning activity carried out at dawn, functions not only as a means of worship but also as a platform for instilling strong moral and ethical values. Meanwhile, anti-bullying education is needed to create a safe and comfortable environment for all individuals. This article outlines how these two approaches can complement each other in building positive character and creating a more harmonious society. Through collaboration between schools, families and communities, it is hoped that a young generation can be formed who has high social awareness and is able to contribute to an environment free from bullying. Thus, this article aims to provide a better understanding of the implementation of dawn education and anti-bullying education in creating strong togetherness in society.